2014
DOI: 10.1016/j.sbspro.2014.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Biolarvacidal Potential of Ipomoea Cairica Extracts Against Key Dengue Vectors

Abstract: Chemicals are used widely as insecticides causing adverse effects to human health and the environment. Natural insecticides derived from plants which is eco-friendly. This study is to assess the efficacy of Ipomoea cairica extract against two different mosquito larvae. Lethal Concentrations (LC 50 ) of petal, leaves and root extract against Ae. albopictus larvae were 20.5, 27.9 and 34.3 mg/L respectively. Lethal concentration (LC 50 ) were found to be lower in Ae. aegypti which were 12.7, 13.6 and 31.9 mg/L re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
1
7
0
4
Order By: Relevance
“…This is due to the moderately low polarity index of acetone (5.1 indexes), which had conversely impacts on high efficacy of bioactivity of compounds which also had been proven in our results. The impact of solvent on the effectiveness of plant extract can be seen between our study and Ishak et al (2014).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…This is due to the moderately low polarity index of acetone (5.1 indexes), which had conversely impacts on high efficacy of bioactivity of compounds which also had been proven in our results. The impact of solvent on the effectiveness of plant extract can be seen between our study and Ishak et al (2014).…”
Section: Discussionsupporting
confidence: 52%
“…Goa et al (2011) indicated that the phenolic contents were influenced by growing conditions; where low temperature enhancing the synthesis of phenylalanine ammonia-lyase (PAL) in plants and may increase the production of phenolics, while high altitude and extended sunlight hours with higher UV radiation positively affect the activity of phenolics synthase (Kishore et al, 2010). Ishak et al (2014) also showed a much lower concentration to cause 85% until 100% larvae mortality using I. cairica leaves extracts, even though those larvae were the same VCRU strain used in the current study. This hypothesizes that the bioactivity of plant extracts is influenced by the geographical origins of the plants and is associated with the dosage applied to the treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saponin bekerja dengan menurunkan tegangan permukaan selaput mukosa traktus digestivus larva sehingga menghambat penyerapan nutrisi, selain itu saponin juga mempunyai efek merusak lapisan kitin pada permukaan larva sehingga ekstrak dapat dengan mudah masuk ke dalam tubuh larva. 37 Jumlah larva Ae. aegypti yang mati setelah pemberian ekstrak daun Bangun-bangun kemudian diuji menggunakan analisis probit untuk mengetahui nilai LC50 dengan menggunakan program minitab.…”
Section: Identifikasiunclassified
“…Ipomoea cairica (L.) Sweet ( ICS ), belonging to the perennial herbaceous vines of the genus, sweet potato of convolvulacea, with a wide distribution nearly all over the world, is used worldwide as folk medicine [10,11,12]. Pharmacological activity research has also revealed that ICS has cytotoxic, larvicidal, anti-inflammatory, and antinociceptive activities [13,14,15,16,17,18,19]. The various bioactivities are relevant to the diverse components in ICS [20].…”
Section: Introductionmentioning
confidence: 99%